How Much Do Taxes Discourage Incorporation? - MACKIE‐MASON, JEFFREY K.; GORDON, ROGER H. (Journal of Finance, 1997)
ABSTRACT The double taxation of corporate income should discourage firms from incorporating. We investigate the extent to which the aggregate allocation of assets and taxable income in the United States between corporate and noncorporate firms responds to the size of this tax distortion during the period 1959–1986. In theory, profitable firms should shift out of the corporate sector when the tax distortion is large, and conversely for firms with tax losses. Our empirical results provide strong support for these forecasts, and imply that the resulting excess burden equals 16 percent of business tax revenue.